Phenotypic characteristics of three indigenous chicken genotypes in Bangladesh (Bangladesh Journal of Livestock Research, 2020)
Poultry contributes the largest parts of animal-source foods. The International Food Policy Research Institute (IFPRI) has estimated that by year 2015, poultry will account for 40% of all animal protein. Indigenous chicken have a capacity to resist disease, able to utilize low quality feeds and their products are preferred by consumers. Their views were collected to indigenous chicken production scenarios and their characteristics and to synthesize the information for gathering knowledge. The review areas were all over Bangladesh but our studied areas were Baraigram, Natore; Sarail, Brahmonbaria and Bandarban Hill tract and genotypes were Indigenous, Aseel and Hilly chicken. The production or management system was backyard scavenging and semi-scavenging type for Indigenous, Hilly and Aseel female chicken but for Aseel male it is used intensive system for breeding program; which was characterized by small flock size.The average number of chicken per house-hold was almost same in Baigram and Sarail (7.93±4.46 and 7.69± 2.75); but lower in Bandarban Hill district (5.11± 1.78). Indigenous, Aseel and Hilly chickens have a large morphological variation. The percent of plumage color of Indigenous chicken was 35% black brownish, 30% brown with black strip, completely black 30% and golden red 5%; in Aseel chicken was as 45% golden red, 30% black brownish, completely black 25% and in Hilly chickens have 50% black brownish, 45% brown with black strip and 5% black plumage color. 90% of indigenous chicken have yellow shank while 10% black shank. All the Aseel chickens have yellow shank. The shank color of Hilly chicken was as 50% yellow, 39% white and 11% black. The study revealed that indigenous chicken and Hilly chicken laid mainly white colored eggs and Aseel chickens laid mainly light brown egg. Feeds were not usually supplemented in all three genotypes reared under scavenging system. Chickens pick up grains such as rice, vegetables, green grass, insect, earthworm etc. from the yard, as chickens have reared under scavenging system. Different types of housing were used for chickens in the selected sites. Approximately 30%, 40% and 60% of farmers kept chickens in their living houses in cases of Indigenous chickens, Aseel and Hilly chicken, respectively. No farmer used artificial lighting for the chickens. So, the study was performed to review indigenous chicken production scenarios may serve as an important base of Ph.D research and may help to take proper planned to conserve of these three genotypes.Bangladesh J. of Livestock Res. 21-25: 10-23, 2018